Circular patch array of microstrip antenna for 2.4GHz / Saiful Hidayat Samak and Norfishah Abd Wahab - Samak, Saiful Hidayat; Abd Wahab, Norfishah
This paper presents the design and analysis of circular patch for linear microstrip array antenna with four elements. The antenna has been designed and fabricated at resonant frequency of 2.4 GHz for digital wireless system applications. The performance of the designed antenna was analyzed in term of return loss, VSWR, percentage bandwidth, radiation pattern, and directivity. The antenna was fabricated on FR-4 laminate with having dielectric constant of 4.9 and substrate thickness is 1.6mm respectively. The antenna characteristics were then measured using vector network analyzer (VNA) and compared with the simulated results using CST software. The results show that the array antenna outperformed in many ways when compared to the single antenna.